Driving simulation: the effects of interactivity and presentation setting - Gabes, Michaela; Mühlberger, Andreas (Frontiers in Virtual Reality, 2024)
Background: Driving simulators are established tools used for different research purposes. Either head-mounted displays (HMDs) or monitors are applied. However, the extent to which the setting (HMD vs. monitors) or the interactivity in driving (active behaviour as a driver or passive behaviour as a co-driver) influences the experience of presence, realism or simulator sickness is not yet entirely clear. Objective: We aimed to compare different conditions to assess the influence of interactivity and presentation setting on the experience of presence, realism, and simulator sickness. Further, different driving performance parameters (e. g. speed perception or sign detection) were aimed to be assessed between the two settings. Methods: Ninety participants were recruited. This was an experimental study (2 x 2 within-between-subject design) with interactivity as within-subject factor (2 levels: active vs. passive) and setting as between-subject factor (2 levels: HMD vs. monitors). As driving scenarios, we selected four specific driving maneuvers that we assume would affect driving behaviour differently depending on the setting. Differences in the experience of presence as well as in the development of simulator sickness were assessed using standardised questionnaires. Results: There was no difference between the two settings regarding presence, realism or simulator sickness. Regarding interactivity, presence was significantly higher in the active compared to the passive condition. The most prominent difference between the two settings was found in the sign detection task where participants wearing an HMD performed worse. Conclusion: The choice of interactivity appears to have a stronger effect on the experience of presence than the setting. Sign detection was worse in the HMD setting probably due to the lower display resolution. These results are relevant for the interpretation of driving simulator studies and the implementation of future studies.